Patients from low-middlProfile and management of patients from low-middle socioeconomic status with thoracic traumae socioeconomic status with thoracic trauma: A prospective observational study on profile and management - Heleen van Aswegen; Ronel Roos; Elizma Haarhoff; Josslyn de Kock; Humairaa Ebrahim; Sameer Tootla; Muhammad Vally; Monika Fagevik Olsén (South African Journal of Physiotherapy)
Background: Pain and shortness of breath (SOB) after thoracic trauma predispose patients to complications and prolonged hospital length of stay (LOS). Patient management after thoracic trauma is seldom reported.